ADSORPTIVE REMOVAL OF PHOSPHATE ONTO IRON LOADED LITCHI CHINENSIS SEED WASTE - Shrestha, Asmita; Poudel, Bhoj Raj; Silwal, Manoj; Pokhrel, Megh Raj (Journal of Institute of Science and Technology, 2019)
Raw and charred Fe(III)-loaded Litchi chinensis seed waste (FeRLW and FeCLW) as bio-adsorbents was investigated to remove phosphate from aqueous solution. Various physico-chemical parameters such as equilibrium time, pH and adsorbent dosage were studied by batch experiment method. The maximum adsorption capacities for phosphate removal by FeRLW and FeCLW were found to be 96.5 mg/g and 100 mg/g, respectively. The experimental results revealed that biomaterials of FeRLW and FeCLW can be used as effective and economically viable adsorbents for the removal of phosphate from waste water.